Ethical Views On Abortion In Thailand Under The Penal Code Amendment Act (No. 28) B.E. 2564 According To The Teaching Of The Catholic Church - Wehapuchan, Ritthikon; Saengthien, Pichet; Prasootsaengchan, Laddawan (Saengtham College Journal, 2025)
The goals of this qualitative research were to 1) compare the ethical views on abortion in Thailand under the Penal Code Amendment Act (No. 28) B.E. 2564 according to the teaching of the Catholic Church; and 2) examine the catechism of the Catholic Church and pastoral care guidelines in relation to abortion in Thailand. Data from a group of 11 experts were gathered through a group discussion. The collected data was examined using content analysis. The findings of this study are as follows: 1.Ethical views on abortion in Thailand under the Penal Code Amendment Act (No. 28) B.E. 2564 according to the teaching of the Catholic Church. The Abortion Law of Thailand (No. 28), 2021, has been amended to ensure that it is consistent with Article 28 of the Kingdom of Thailand’s Constitution, which emphasizes the protection of the rights and dignity of pregnant women and places value on the life of a human who is to be born (fetus). While the Catholic Church reaffirms the original doctrine against abortion in all instances and focuses on the value of human action, the ultimate goodness used as a criterion for abortion is found not in the balance of the woman’s bodily freedom and the right to life of the fetus but in God as the creator of life and the owner of life. Therefore, the life of the unborn child cannot be violated. According to the Fifth Commandment, "You shall not kill," which governs human behavior, direct abortion, or the intentional killing of a human being in the womb, is always morally wrong because of the right to life as a person. The Church attaches the canonical penalty of excommunication to this crime against human life. "A person who procures a completed abortion incurs excommunication" (Code of Canon Law, can. 1398). The teachings of the Catholic Church aim for the ultimate dignity of life, which must be protected with the utmost care from the moment of conception. Human beings are to be respected according to God’s commandment; this includes fetuses, pregnant women, and those involved in abortion. 2.Guidance of the catechism of the Catholic Church and pastoral care of abortion in Thailand. 2.1 Advisory of catechism of Catholic Church in Thailand 1) Official documents about abortion written in simple language should be published and made available to Christians. 2) There should be explanations of various doctrines about abortion in catechism courses, homilies, and mass media. 3) All Christians should have access to the abortion doctrine in order to learn more about it, understand how to prevent it, and discover how to address it. 4) The school has to teach the Catholic teachings on abortion, beginning from Grade 7, and continue through college. 5) The Catholic Church in Thailand should provide a clear form of teaching or curriculum to teach Christians about abortion in a Christian context. 6) To assist those who have experienced problems related to abortion or those who need guidance with an undesired pregnancy and abortion, appropriate catechism teaching methods should be utilized. 7) Doctors, nurses, and other health-care workers should research and update their knowledge of Catholic teachings. This can help them to practice their moral obligation and to examine their consciences in this matter. 8) Forming of conscience regarding to the teaching of the Church is encouraged for those who want to abort and those who are unintentionally pregnant, including all Christian to understand the teaching and has concise conscience. 2.2 Pastoral guidance on abortion in the Catholic Church of Thailand. 1) Every Christian must build a strong relationship with Jesus Christ and follow to His teachings. 2) The Church should encourage Christians to learn about the fundamental Church teachings in order for them to understand the origin of life and the dignity of human beings. 3) There should be ongoing pastoral care in all stages of life for all groups of Christians, especially those who have problems with unwanted pregnancy or abortion, so that they will be open-minded and attentive to the Church’s teachings consistently. 4) Priests, religious leaders, and catechists are responsible for pastoring Christians to understand human values and dignity. They should be involved in pastoral work and cultivate good moral values and ethics among children and youth in their own communities. 5) Pastoral care should be provided to those associated with this ministry to ensure that they will receive clear guidance, encouragement, and the courage to constantly live their lives in accordance with their right conscience. 6)Medical pastoral attention is needed for those included in the case for they will be able to use their conscience correctly according to the teaching of the Church.